Pathological study of Stachybotrys chartarum that isolated from baths floor in Babylon province on some respiratory and digestive organs in white mice(Balb/c) - K . Al-Mansoori, Abbas (Al-Qadisiyah Journal of Pure Science, 2018)
Stachybotrys chartarum is filamentous fungi that cause respiratory system infection in human and animals . This study was aimed to evaluate histological changes in some respiratory and digestive organs such as pharynx, trachea and lung induced by this fungus suspension . Detection of Stachybotrys chartarum fungus confirmed by cultured random samples that collected in clean containers from baths floor on potato dextrose agar in room temperature for 7-14 days. Then the suspension of positive samples of this fungus diluted by normal saline and counted the spores by using hemocytometer before used experimentally in lab animals (Balb mice) to study histological changes in some respiratory and digestive organs . Twelve mice used in this study divided into two groups . first group consist of six mice injected orally with 0.5 ml from one positive sample of fungus suspension contain 2Ã—103 spore / mm3(for month : one dose daily) according to count of hemocytometer to evaluate some pathological changes in pharynx ,trachea and lung .Second group injected orally with 0.5 ml from phosphate buffer saline only. The results revealed that no changes in the pharynx of mice infected with0.5 ml contain 2Ã—103 spore / mm3 from Stachybotrys chartarum fungus suspension. the lung of group mice treated with same concentration of fungus has interstitial pneumonia with thickening of inter alveolar space due to infiltration and chronic inflammatory cells especially mononuclear cell. While the trachea of group mice treated with same concentration of fungus suffering sub mucosal chronic inflammatory cells and infiltration with increase thickness of mucosal basal layer .